Review: Problem Based Learning Memengaruhi Peningkatan Sikap Ilmiah pada Mata Pelajaran Kimia - Kamila, Nadzifatul; Rinaningsih, Rinaningsih (Chemistry Education Review (CER), 2021)
Problem based learning is a learning model that can improve students' attitudes. This article aims to review the results of the problem based learning model in improving the scientific attitudes of students in chemistry subjects. Problem based learning is a series of learning activities that emphasize the process of solving a problem faced scientifically. The method of writing in this article uses meta-analysis, by comparing information in the form of the pretest and pottest values in several similar articles. Based on the results of the analysis of several articles collected, the problem based learning model is able to improve scientific attitudes in chemistry subjects. The results of the comparison of the average increase of the 18 articles that were observed obtained a value of 18.27%. The paired sample test results obtained an average pretest of 56.03 while the average posttest of 74.29. Another result of the effect size test is that it is 1.390 in the strong category. The results of this article indicate that problem-based learning can effectively improve students' scientific attitudes in chemistry subjects.